How Innovative is Singapore in High Technology Industry Cluster? An Empirical Study of Annual Reports of High Technology Firms - Cheung, Yau Kiu Ruby (2006)
As a small country lacking of natural resources, Singapore has been developing innovation-based industry, which is highly associated with high technology. High technology sector has become an important pillar of today's Singapore economy. This paper is to evaluate how innovative Singapore is. The evaluation is conducted through empirical study of Singapore technology firms' annual reports, discussion of Singapore national innovation policy and the world recognition of Singapore's economic performance. The companies selected are within the high technology cluster to which the Singapore National Innovation System (NIS) is applied.